Antioxidant Mechanism of Lactiplantibacillus plantarum KM1 Under H2O2 Stress by Proteomics Analysis - Tian, Yuan; Wang, Yu; Zhang, Nan; Xiao, Minmin; Zhang, Jing; Xing, Xinyue; Zhang, Yue; Fan, Yuling; Li, Xia; Nan, Bo; Wang, Yuhua; Liu, Jingsheng (Frontiers in Microbiology, 2022)
Lactiplantibacillus plantarum KM1 was screened from natural fermented products, which had probiotic properties and antioxidant function. The survival rate of L. plantarum KM1 was 78.26% at 5 mM H2O2. In this study, the antioxidant mechanism of L. plantarum KM1 was deeply analyzed by using proteomics method. The results demonstrated that a total of 112 differentially expressed proteins (DEPs) were screened, of which 31 DEPs were up-regulated and 81 were down-regulated. KEGG enrichment analysis indicated that DEPs participated in various metabolic pathways such as pyruvate metabolism, carbon metabolism, TCA cycle, amino acid metabolism and microbial metabolism in diverse environments. These metabolic pathways were related to oxidative stress caused by H2O2 in L. plantarum KM1. Therefore, the antioxidant mechanism of L. plantarum KM1 under H2O2 stress provided a theoretical basis for its use as a potential natural antioxidant.